HUBUNGAN KEBERADAAN TEMPAT PERINDUKAN NYAMUK DAN TINGKAT PENGETAHUAN MASYARAKAT TERHADAP KEJADIAN MALARIA DI DESA SUKAJAYA LEMPASING KABUPATEN PESAWARAN PROVINSI LAMPUNG TAHUN 2015 - Dwi Nopriyanto; Rr. Tutik Sri Hariyati; Titin Ungsianik (Holistik Jurnal Kesehatan, 2019)
PUTTING ORLANDO'S THEORY INTO PRACTICE: APPROACH TO INTEGRATED DEVELOPMENTBackground: Documentation of integrated patient development records has not been optimal due to lack of understanding of nurse in writing, and uniformity of the content of writing rules, and there has not yet optimal support from the head nurse.Purpose: This study is to identify the impact of strengthening the role of the head nurse using the Orlando’s theory approach on the implementation in documented of integrated patient development records.Methods: Pre experimental design with one group pre test and post test design without control, samples on this study are 115 documents of integrated patient development record, cluster sampling technique, analyzed used with Wilcoxon, Spearman and Kruskal Wallis test analysis.Results: Showing that the role strengthening of the head nurse with the Orlando’s theory approach significantly improves the quality of implementation for documented of integrated patient development record (p=0.0001; α=0,025). Conclusion: The nursing abilities of the implementers increased significantly in the implementation in documented of integrated patient development record.Recommendation: As reference to make policies, assistance, evaluation and monitoring of nursing managers and development through workshops on the role of the head nurse and implementation documentation of integrated patient development records.Keywords: Integrated patient development records, role of the head nurse, Orlando’s theoryPendahuluan: Dokumentasi catatan perkembangan pasien terintegrasi belum optimal karena kurangnya pemahaman perawat dalam melakukan penulisan, dan keseragaman dari isi kaidah penulisan, serta belum optimalnya dukungan dari kepala ruang.Tujuan: Mengidentifikasi pengaruh penguatan peran kepala ruang dengan pendekatan Teori Orlando terhadap pelaksanaan pendokumentasian catatan perkembangan pasien terintegrasi.Metode: Pre eksperiment design dengan one group pre test and post test design without control, dengan sampel 115 dokumen catatan perkembangan pasien terintegrasi, teknik cluster sampling, melalui analisis Wilcoxon, Spearman dan Kruskal Wallis test.Hasil: Penguatan peran kepala ruang dengan pendekatan Teori Orlando meningkatkan kualitas pelaksanaan pendokumentasian catatan perkembangan pasien terintegrasi secara bermakna (p=0,0001; α=0,025).Simpulan: Kemampuan perawat pelaksana meningkat bermakna dalam pelaksanaan pendokumentasian catatan perkembangan pasien terintegrasi melalui penguatan peran kepala ruang dengan pendekatan Teori Orlando.Rekomendasi: Perlunya kebijakan, pendampingan, evaluasi, dan monitoring dari manajer keperawatan serta pengembangan melalui workshop penerapan peran kepala ruang dan pelaksanaan pendokumentasian catatan perkembangan pasien terintegrasi.